Equations of a Synchronous Machine in Phase Coordinates for Asymmetrical Short Circuits and their Solutions - Guliyev, Huseyngulu; Ibrahimov, Famil (International Journal of Advanced Engineering Research and Science, 2023)
A methodology is proposed for studying, using digital technology, asymmetrical transient modes of a synchronous generator operating on infinite power systems. The initial equations of a synchronous machine and sequential transformations for their solution are presented. Differential equations of synchronous machines are compiled in phase coordinates. When solving the equations, the parameters of the electrical network included between the generator and the system are taken into account. The results of calculations using the obtained equations for the 14-node IEEE test circuit are presented, confirming the effectiveness of this approach.